2022
DOI: 10.3389/fnut.2022.913571
|View full text |Cite
|
Sign up to set email alerts
|

Diet Containing Soy Protein Concentrate With Low and High Isoflavones for 9 Weeks Protects Against Non-alcoholic Fatty Liver Steatosis Using Obese Zucker Rats

Abstract: Non-alcoholic fatty liver disease (NAFLD), is one of the main liver diseases in the US and the world which often is related to obesity. Previously, we reported short- and long-term consumption of soy protein isolate diet with high isoflavones can reduce liver steatosis in the male and female obese Zucker rat model. However, the effects of high vs. low soy isoflavones on NAFLD is less known. The objectives of the present study were to examine the role of isoflavones levels in soy protein concentrate diets on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Given the current state of treatment for NAFLD/MAFLD, daidzein may be a potential therapeutic option. Recent research has demonstrated that soy protein concentrates and related isoflavones play an important role in lowering blood lipids, reducing hepatic steatosis, and improving the symptoms of NAFLD ( 66 , 67 ). A cross-section study of 17,685 US adults also showed a negative association between the consumption of flavonoids and FLI ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the current state of treatment for NAFLD/MAFLD, daidzein may be a potential therapeutic option. Recent research has demonstrated that soy protein concentrates and related isoflavones play an important role in lowering blood lipids, reducing hepatic steatosis, and improving the symptoms of NAFLD ( 66 , 67 ). A cross-section study of 17,685 US adults also showed a negative association between the consumption of flavonoids and FLI ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SPC-LIF diet was included to test whether any observed effect was due to the protein or the isoflavone content of SPC. All diets were prepared by Archer Daniels Midland (AMD) (Decatur, IL, USA) with detailed compositions reported previously [23]. The SPC-LIF diet had 0.154 mg isoflavone/g protein with an aglycone component of approximately 0.16 mg/g protein.…”
Section: Experimental Designmentioning
confidence: 99%
“…To balance amino acid profile, L-cystine was added at 3 g/kg to the casein diet and 1.2 g/kg to SPC-LIF and SPC-HIF diets and L-methionine was added at 2.2 g/kg to SPC-LIF and SPC-HIF diets. Diets were isocaloric and isonitrogenous [23]. After 10 weeks of feeding one of the three diets (CAS, SPC-LIF, or SPC-HIF), rats were anesthetized with carbon dioxide and euthanized by decapitation.…”
Section: Experimental Designmentioning
confidence: 99%
“…Whereas obese rats had significantly greater liver steatosis score than lean rats, both soy protein concentrate with low isoflavones and and soy protein concentrate with high isoflavones intake resulted in reduction in steatosis score compared to control group. Authors also suggested that soy protein concentrate with isoflavones consumption may protect against liver steatosis and these results are greater with a higher concentration of isoflavones [27].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%